First genome-scale insights into the virulence of the snow mold causal fungus Microdochium nivale - Ivan Tsers; Ekaterina Marenina; Azat Meshcherov; Olga Petrova; Olga Gogoleva; Alexander Tkachenko; Natalia Gogoleva; Yuri Gogolev; Evgenii Potapenko; Olga Muraeva; Mira Ponomareva; Viktor Korzun; et al. (IMA Fungus)
Abstract Pink snow mold, caused by a phytopathogenic and psychrotolerant fungus, Microdochium nivale, is a severe disease of winter cereals and grasses that predominantly occurs under snow cover or shortly after its melt. Snow mold has significantly progressed during the past decade, often reaching epiphytotic levels in northern countries and resulting in dramatic yield losses. In addition, M. nivale gradually adapts to a warmer climate, spreading to less snowy territories and causing different types of plant diseases throughout the growing period. Despite its great economic importance, M. nivale is poorly investigated; its genome has not been sequenced and its crucial virulence determinants have not been identified or even predicted. In our study, we applied a hybrid assembly based on Oxford Nanopore and Illumina reads to obtain the first genome sequence of M. nivale. 11,973 genes (including 11,789 protein-encoding genes) have been revealed in the genome assembly. To better understand the genetic potential of M. nivale and to obtain a convenient reference for transcriptomic studies on this species, the identified genes were annotated and split into hierarchical three-level functional categories. A file with functionally classified M. nivale genes is presented in our study for general use. M. nivale gene products that best meet the criteria for virulence factors have been identified. The genetic potential to synthesize human-dangerous mycotoxins (fumonisin, ochratoxin B, aflatoxin, and gliotoxin) has been revealed for M. nivale. The transcriptome analysis combined with the assays for extracellular enzymatic activities (conventional virulence factors of many phytopathogens) was carried out to assess the effect of host plant (rye) metabolites on the M. nivale phenotype. In addition to disclosing plant-metabolite-upregulated M. nivale functional gene groups (including those related to host plant protein destruction and amino acid metabolism, xenobiotic detoxication (including phytoalexins benzoxazinoids), cellulose destruction (cellulose monooxygenases), iron transport, etc.), the performed analysis pointed to a crucial role of host plant lipid destruction and fungal lipid metabolism modulation in plant-M. nivale interactions.